2016
DOI: 10.21037/jgo.2016.06.13
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous biliary drainage catheter insertion in patients with extensive hepatic metastatic tumor burden

Abstract: Laboratory data before and after PBD insertion were compared. Survival and outcomes analysis performed.A subanalysis was performed on patients with CT-demonstrated catheter traversal of tumoral tissue.Results: A PBD catheter was successfully inserted in all patients. The mean serum bilirubin level decreased significantly from 10.9±6.4 mg/dL immediately prior to PBD insertion to 7.1±5.6 mg/dL (P<0.001) within one month post PBD insertion. Four patients (11%) demonstrated normalization of bilirubin levels to les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…We had cent percent technical success in our study, higher than that of similar experience of Kronsten et al 14 and Haq et al 15 We could reduce bilirubin to > 50% in all the cases as compared to 68.2% only in the same study by Kronsten et al 14 Similar findings was seen in the experience of Haq et al 15 Complication rate in our study was similar to the study by Kronsten et al 14 but less as compared to the experience of Haq et al 15 Thirty day mortality was nil in our study as compared to 28.8% in the study of Kronsten et al 14 and 5% in the study of Haq et al 15 Mean survival rate in our study was 7.1 months, which is significantly higher than that of similar experience of Langman et al 16 , Kasuga et al 17 , Iwasaki et al 18 and Haq et al 15 Early stent patency rate in our study is similar to that of study done by Liet al 12 , however, 6 month stent patency rate was slightly lower in our study (45% vs 53%). We are still following up the patients, and some of the procedures are done <3 months back.…”
Section: Discussionsupporting
confidence: 79%
“…We had cent percent technical success in our study, higher than that of similar experience of Kronsten et al 14 and Haq et al 15 We could reduce bilirubin to > 50% in all the cases as compared to 68.2% only in the same study by Kronsten et al 14 Similar findings was seen in the experience of Haq et al 15 Complication rate in our study was similar to the study by Kronsten et al 14 but less as compared to the experience of Haq et al 15 Thirty day mortality was nil in our study as compared to 28.8% in the study of Kronsten et al 14 and 5% in the study of Haq et al 15 Mean survival rate in our study was 7.1 months, which is significantly higher than that of similar experience of Langman et al 16 , Kasuga et al 17 , Iwasaki et al 18 and Haq et al 15 Early stent patency rate in our study is similar to that of study done by Liet al 12 , however, 6 month stent patency rate was slightly lower in our study (45% vs 53%). We are still following up the patients, and some of the procedures are done <3 months back.…”
Section: Discussionsupporting
confidence: 79%
“…[2,12] Previous reports on drainage of obstructive jaundice due to various malignancies showed that the presence of liver metastases was associated with a lower rate of successful drainage [19,20] and that serum bilirubin level rarely normalizes in patients with an extensive hepatic metastatic tumor burden, as a result of mechanical biliary obstruction and parenchymal replacement. [21] It illustrates the often advanced stage and severity of the disease when obstructive jaundice becomes manifest. Adverse events occurred in 19% to 39% of patients and was mostly cholangitis.…”
Section: Discussionmentioning
confidence: 99%
“…For these reasons, surgical by-pass applications can be recommended in patients with low risk in the palliative treatment of patients with malignant biliary obstruction such as pancreatic carcinoma. [14] PBD is a useful and effective palliative treatment option in patients considered inoperable. [8] However, the effect of routine preoperative decompression on decreasing morbidity and mortality in cases dependent on different etiologies, or who have not lost the chance of operability or benign and uncomplicated, is controversial.…”
Section: Discussionmentioning
confidence: 99%